Details of the "Attack" Movement on the Territory of Turkey During the Soviet Union and its Consequences - oglu, Kamoliddinov Farrukh Burxoniddin (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the "Attack" movement in Turkestan in the first half of the twentieth century, the liberation movement for women, and the pursuit of the ugly goals of the Soviet Union behind this movement. Along the way, they talk about the atrocities and violence they committed. Why do some women in Turkestan agree with these proposals, but who are well aware of their dignity and oppose "freedom" and are steadfast martyrs in their decisions information is given.